(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The article examines the behavioral aspects of the triad model of social organization. In addition to the pressure relationship in the behavior of triads, the support relationship is highlighted, which specifies some features of relations in society. A new concept of organizational triad is introduced, which better reflects in society. For this triad, the laws of its behavior are considered, which are formulated in the theorem on fixed points of the triad and the theorem on the convergence of the triad to fixed points. Some issues of triad decomposition are also considered. In conclusion, general conclusions on the materials of the article are discussed.